A method for preparing a sustained-release enhanced cement grinding aid
Through the combination of different esterization and polyoline amine compounds to form a slow -release enhanced cement abrasive, solve the problem of poor effects and enhancement of material failure during the powder grinding process of existing cement abrasives. The excellent grinding and enhanced effects in the process of cement powder grinding and hydration.
Patent Information
- Application Number
- CN202311265695.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing cement agitator has a single molecular structure and cannot effectively match the cement grinding process, resulting in limited grinding effect and the enhancement substances are buried during the hydration process, and failure cannot continuously provide enhanced effects.
The combination of esters of different esters and polyol amoramine is used to form monocles, diacerne, and trigeminals through esterization reactions. The surface of the cement particles interacts, forming a slow -release enhanced cement abrasive.
Achieve the excellent grinding effect in the cement powder grinding process, promote the hydration of the difficulty and hydrated iron alumic acid, improve the strength of the cement period, and continuously release new alcoholine through the continuous hydrolysis of the ester group. Compounds continue to promote cement hydration and achieve the effect of slow release.
Smart Images

Figure BDA0004474225060000071 
Figure BDA0004474225060000081 
Figure BDA0004474225060000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a method for preparing a cement grinding aid. Background Art
[0002] At present, my country is the country with the largest cement production in the world, with a cement production of 2.1 billion tons in 2022. Cement grinding is an important part of cement production. The cement grinding equipment commonly used in my country is ball mill, with an energy utilization rate of less than 15%, and most of the electric energy is consumed in ineffective heat. Adding enhanced grinding aids in the cement production process can not only help with grinding, reduce the fineness of cement grinding, increase the hourly output and reduce power consumption, but also promote cement hydration, increase cement strength and increase the use of admixtures. Therefore, the use of cement grinding aids is of great significance to the green and low-carbon development of the cement industry.
[0003] At present, the reported cement grinding aid technology is mainly composed of alcohol amines, polyols, and inorganic salts as raw materials, which are compounded in different proportions. The application effect of grinding aids has encountered bottlenecks due to the limitation of raw material types. Organic matter can give grinding aids new properties due to the designability of its molecular structure, and has obvious advantages in performance improvement. Using molecular structure design and synthetic methods to prepare new substances as cement grinding aids is an effective way to break through the bottleneck of application effect.
[0004] The existing grinding aids are mostly small molecule organic substances with a common molecular weight of 70 to 200 g / mol and a single molecular size. Cement grinding is a process in which material particles change from large to small, which cannot match the entire grinding process and has limited effect on improving efficiency during the grinding process.
[0005] The reinforcing substances in the existing grinding aids are mostly alcoholamine substances, which achieve the reinforcing effect by complexing the metal ions produced by cement hydration to increase the dissolution rate and promote cement hydration. The grinding aids after complexing the metal ions will be "buried" in the hydration products due to the continuous hydration of cement and become ineffective, and cannot continue to provide reinforcing effects. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a sustained-release enhanced cement grinding aid, which utilizes the molecular size effect of esters with different esterification degrees in combination with other grinding aid components to exert a synergistic effect, and has an excellent grinding aid effect; effectively promotes the hydration of tetracalcium aluminoferrate that is difficult to hydrate in cement, and while the enhancing components exert their enhancing effects, esters with different esterification degrees are continuously hydrolyzed to continuously release new alcoholamine compounds, thereby achieving a sustained-release enhancement effect and effectively improving the strength of cement at all ages.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0008] A method for preparing a sustained-release enhanced cement grinding aid comprises the following steps:
[0009] Mix 2-amino-5-thiocyanatobenzoic acid and polyol amine A in a reaction kettle, stir and heat to 80-100° C. under nitrogen protection;
[0010] Add chitosan sulfate catalyst and water-carrying agent, stir and heat to 110-130°C, and carry out esterification reaction for 2-8 hours. During the reaction, separate the water generated by the reaction. Remove the water-carrying agent after no more water is separated.
[0011] Polyol amine B was added to adjust the pH value of the system to 6-7 to obtain a sustained-release enhanced cement grinding aid.
[0012] According to the above scheme, the molar ratio of 2-amino-5-thiocyanatobenzoic acid to polyol amine is (1-3):1.
[0013] According to the above scheme, the amount of chitosan sulfate catalyst used is 2-4% of the mass of 2-amino-5-thiocyanatobenzoic acid.
[0014] According to the above scheme, the amount of the water-carrying agent is 15-20% of the mass of 2-amino-5-thiocyanatobenzoic acid.
[0015] According to the above scheme, the polyol amine A is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, and triisopropanolamine, or any mixture thereof; the polyol amine B is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, and triisopropanolamine, or any mixture thereof.
[0016] According to the above scheme, the water-carrying agent is one of benzene and toluene.
[0017] According to the above scheme, the preparation method of the chitosan sulfate catalyst comprises the following steps:
[0018] Chitosan is dissolved in an acetic acid solution, diluted sulfuric acid is added to precipitate it and the precipitate is filtered, the precipitate is washed with water until it is neutral, then rinsed with an organic solvent, and dried to obtain a chitosan sulfate catalyst.
[0019] According to the above scheme, the weight average molecular weight of chitosan is 2×10 5 ~5×10 5 g / mol.
[0020] According to the above scheme, the 2-amino-5-thiocyanatobenzoic acid is added to the reactor in three times, one third of the total amount is added before the start of the esterification reaction, and then one third of the total amount is added every one third of the esterification reaction until all the addition is completed.
[0021] According to the above scheme, the dosage of the sustained-release enhanced cement grinding aid is 0.02-0.10wt% of the cement.
[0022] The carboxyl group in the structure of 2-amino-5-thiocyanatobenzoic acid is a strong calcium adsorption group, the amino group can be complexed with aluminum and iron, and the thiocyanato group is a strong iron complexing group. In the cement grinding stage, each group can be adsorbed on the calcium-oxygen, aluminum-oxygen, and iron-oxygen bond-breaking surfaces produced by cement grinding, reducing the mineral surface energy to reduce the hardness, shielding the bond-breaking surface charge to avoid the bond-breaking electrostatic adsorption, and adsorbing on the mineral surface to form a film to improve the powder fluidity, thereby playing a good grinding aid role. In the cement contact water hydration stage, each group effectively complexes calcium, aluminum, and iron, improves its dissolution rate and dissolution amount, promotes cement hydration, and improves the strength of cement hydration products. The molar ratio of 2-amino-5-thiocyanatobenzoic acid and polyolamine compound used in the present invention is (1-3): 1, and the remaining 2-amino-5-thiocyanatobenzoic acid can be used as an enhanced grinding aid component without having to be separated separately while ensuring that the alcohol amine is completely esterified, and the raw materials can be effectively utilized.
[0023] The invention adopts chitosan sulfate as an esterification reaction catalyst, which has the advantages of strong catalytic activity, avoiding side reactions and high yield compared with other catalysts. In addition, chitosan sulfate has multiple hydroxyl groups, multiple amino groups and sulfate groups, which can play a good grinding aid and enhancement role on cement. After the esterification reaction is completed, it does not need to be separated and can be used as a grinding aid and enhancement material, thereby solving the problem that the esterification reaction catalyst is difficult to separate.
[0024] The trivalent hydroxyl group and the central nitrogen atom in the structure of the polyol amine compound can be adsorbed on the surface of cement particles to play a grinding aid role; at the same time, the unshared electron pair on the nitrogen atom can be complexed with aluminum and iron, so that the diffusion of metal ions in the slurry is accelerated, the dissolution rate of the intermediate mineral is accelerated, the cement hydration reaction is promoted, and the cement strength is improved. The present invention uses a polyol amine compound to neutralize the unreacted 2-amino-5-thiocyanatobenzoic acid. On the one hand, the pH value of the system can be made 6 to 7, which can effectively avoid the hydrolysis reaction of the esterification product; on the other hand, it can play a grinding aid and enhancement role.
[0025] The present invention adopts 2-amino-5-thiocyanatobenzoic acid and polyol amine compounds to undergo esterification reaction, and monoesters, diesters and triesters can be generated when the molar ratio of 2-amino-5-thiocyanatobenzoic acid to polyol amine compounds is (1-3):1. The amino groups brought by 2-amino-5-thiocyanatobenzoic acid in the esterification product structure and the hydroxyl groups and nitrogen brought by the polyol amine compounds in the monoester and diester can play a good grinding aid effect. At the same time, the ternary "forked" amino group in the triester has a stronger adsorption effect and a better grinding aid effect. The grinding aid is adsorbed on the surface of cement grinding particles to play a "wedge" role, reduce the particle strength and thus achieve a grinding aid effect. The monoesters, diesters and triesters prepared in the present invention each have different molecular sizes, and the grinding of cement is a process in which particles change from large to small. Esterified products of different molecular sizes can play a matching grinding aid effect at different stages of grinding, and the grinding aid effect is better.
[0026] When no reinforcing agent is added to cement, due to the slow dissolution of iron ions in the cement mineral tetracalcium aluminoferrate and the small amount of dissolution, its contribution to the strength of cement paste through hydration generally occurs at 28 days or even later and the contribution is small. The N≡C-S- in the structure of the esterification product prepared by the present invention can coordinate with iron ions to form a stable complex structure through the lone pair of electrons of S and N as electron donors, which can effectively promote the dissolution of iron ions in tetracalcium aluminoferrate, increase the dissolution rate and increase the total amount of dissolution, promote the hydration of tetracalcium aluminoferrate, and generate more hydration products that are beneficial to the strength of cement, thereby achieving the improvement of the strength of cement at all ages. The present invention utilizes 2-amino-5-thiocyanatobenzoic acid to carry out esterification of hydroxyl groups in the structure of polyol amines to different degrees. On the one hand, the early hydration of cement can be reduced to "bury" the adsorption of polyol amines in the hydration products and lose their effect; on the other hand, the ester groups will continuously undergo hydrolysis reaction under the alkaline conditions generated by cement hydration to release alcohol amine compounds. The time required for complete hydrolysis of esters with different esterification degrees is different. The continuous hydrolysis of monoesters, diesters and triesters continuously releases new alcohol amine compounds, continuously promotes cement hydration, thereby achieving a sustained-release enhancement effect and effectively improving the strength of cement at all ages.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The slow-release enhanced cement grinding aid prepared by the present invention utilizes the molecular size effect of esters with different esterification degrees and combines with other grinding aid components to exert synergistic effects, and has a more excellent grinding aid effect;
[0029] 2. The slow-release enhanced cement grinding aid prepared by the present invention effectively promotes the hydration of the difficult-to-hydrate tetracalcium aluminoferrate in cement. While the enhancing components exert their enhancing effects, the esters with different esterification degrees are continuously hydrolyzed to continuously release new alcoholamine compounds, thereby achieving a slow-release enhancement effect and effectively improving the strength of cement at all ages.
[0030] 3. The slow-release enhanced cement grinding aid prepared by the present invention makes full use of various substances after each raw material and esterification reaction, and has a higher cost performance;
[0031] 4. The method for preparing the sustained-release enhanced cement grinding aid provided by the present invention is mature, safe, and well controllable, and can be industrialized;
[0032] 5. The sustained-release enhanced cement grinding aid prepared by the method for preparing the sustained-release enhanced cement grinding aid provided by the present invention can be used directly without further compounding, thereby reducing the production steps and the product quality risks caused by the large number of production steps. DETAILED DESCRIPTION
[0033] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention. The following specific examples are only some preferred embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, modifications, substitutions and improvements made by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0034] A method for preparing a sustained-release enhanced cement grinding aid is provided in a specific embodiment:
[0035] 2-Amino-5-thiocyanatobenzoic acid and polyol amine compounds are added to a reaction kettle in proportion, and the temperature is raised to 80-100° C. while stirring under nitrogen protection. Chitosan sulfate catalyst and water-carrying agent are added, and the temperature is raised to 110-130° C. while stirring. The esterification reaction is carried out for 2-8 hours. During the reaction, the water generated by the reaction is separated. After no more water is separated, the water-carrying agent is removed, and the polyol amine compound is added to adjust the pH value of the system to 6-7 to obtain a slow-release enhanced cement grinding aid.
[0036] Specific implementation method provides the sources of the test materials, unless otherwise specified, all of which can be obtained through commercial channels.
[0037] Specific implementation method: The source of the 2-amino-5-thiocyanatobenzoic acid is obtained from the market, and the manufacturer is American Custom Chemicals Corporation.
[0038] As a preferred embodiment, the molar ratio of the 2-amino-5-thiocyanatobenzoic acid to the polyol amine compound is (1-3):1.
[0039] In the optimized scheme, 2-amino-5-thiocyanatobenzoic acid is added to the reactor in three times, one third of the total amount is added before the start of the esterification reaction, and then one third of the total amount is added every one third of the esterification reaction until all is added.
[0040] As a preferred solution, the amount of the catalyst is 2-4% of the mass of 2-amino-5-thiocyanatobenzoic acid.
[0041] As a preferred solution, the amount of the water-carrying agent is 15-20% of the mass of the thiocyanatobenzoic acid compound.
[0042] As a preferred embodiment, the polyol amine compound is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, triisopropanolamine, or any mixture thereof.
[0043] As a preferred embodiment, the water-carrying agent is one of benzene and toluene.
[0044] As a preferred embodiment, the preparation method of the chitosan sulfate catalyst comprises the following steps:
[0045] The molecular weight is 3×10 5 g / mol chitosan is completely dissolved in 2% acetic acid solution, and 2% acetic acid solution is continued to be slowly added. During this period, the pH value is measured by a pH meter until the pH value of the solution is 3, and then the addition of 2% acetic acid solution is stopped. The mixture is kept at a constant temperature of 50°C for 2 hours, and dilute sulfuric acid is added to completely precipitate the mixture. The mixture is filtered under reduced pressure, washed with water to a pH value of 7, and rinsed with a mixture of ethanol and acetone to remove water. The mixture is dried in a vacuum oven at a constant temperature of 60°C to a constant weight to obtain a chitosan sulfate catalyst.
[0046] As a preferred solution, the dosage of the sustained-release enhanced cement grinding aid is 0.03% of the cement.
[0047] Example 1
[0048] 1 mol of 2-amino-5-thiocyanatobenzoic acid and 1 mol of triethanolamine were added to the reactor in proportion. Under nitrogen protection, the temperature was raised to 80°C with stirring. 3.88 g of chitosan sulfate catalyst and 29.13 g of benzene were added. The temperature was continued to be raised to 110°C with stirring. The esterification reaction was carried out for 2.0 h. During the reaction, the water generated by the reaction was separated. When no more water was separated, the benzene was removed. Diethanol monoisopropanolamine was added to adjust the pH value of the system to 6.0, and a sustained-release enhanced cement grinding aid was obtained.
[0049] Example 2
[0050] 1.1 mol of 2-amino-5-thiocyanatobenzoic acid and 1 mol of diethanol monoisopropanolamine were added to the reactor in proportion. Under nitrogen protection, the temperature was raised to 85°C with stirring. 4.91 g of chitosan sulfate catalyst and 32.69 g of toluene were added. The temperature was continued to be raised to 111°C with stirring. The esterification reaction was carried out for 3.5 hours. During the reaction, the water generated by the reaction was separated. When no more water was separated, the toluene was removed. Hydroxyethyl diisopropanolamine was added to adjust the pH value of the system to 7.0, and a sustained-release enhanced cement grinding aid was obtained.
[0051] Example 3
[0052] 0.5 mol 2-amino-5-thiocyanatobenzoic acid and 1 mol hydroxyethyldiisopropanolamine were added to the reactor in proportion, and the temperature was raised to 87°C while stirring under nitrogen protection. 7.28 g chitosan sulfate catalyst and 46.03 g benzene were added, and the temperature was continued to be raised to 120°C while stirring. After the esterification reaction was carried out for 1.5 hours, 0.5 mol 2-amino-5-thiocyanatobenzoic acid was added to the reactor again. After the esterification reaction was carried out for 3.0 hours, 0.5 mol 2-amino-5-thiocyanatobenzoic acid was added to the reactor again, and the esterification reaction was continued for 1.5 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the benzene was removed, and diethanol monoisopropanolamine was added to adjust the pH value of the system to 6.5 to obtain a sustained-release enhanced cement grinding aid.
[0053] Example 4
[0054] 0.6 mol 2-amino-5-thiocyanatobenzoic acid and 1 mol triisopropanolamine were added to the reactor in proportion, and the temperature was raised to 90°C while stirring under nitrogen protection. 9.44 g chitosan sulfate catalyst and 56.63 g toluene were added, and the temperature was continued to be raised to 125°C while stirring. After the esterification reaction was carried out for 2.1 hours, 0.6 mol 2-amino-5-thiocyanatobenzoic acid was added to the reactor again. After the esterification reaction was carried out for 4.2 hours, 0.6 mol 2-amino-5-thiocyanatobenzoic acid was added to the reactor again, and the esterification reaction was continued for 2.1 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the toluene was removed, and triethanolamine was added to adjust the pH value of the system to 6.8 to obtain a sustained-release enhanced cement grinding aid.
[0055] Example 5
[0056] 2.0 mol of 2-amino-5-thiocyanatobenzoic acid, 0.1 mol of triethanolamine and 0.9 mol of diethanol monoisopropanolamine were added into the reaction kettle in proportion. Under nitrogen protection, the temperature was raised to 92°C with stirring. 11.65 g of chitosan sulfate catalyst and 67.20 g of benzene were added. The temperature was raised to 130°C with stirring. The esterification reaction was carried out for 7.2 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the benzene was removed. Hydroxyethyl diisopropanolamine was added to adjust the pH value of the system to 6.9, and a sustained-release enhanced cement grinding aid was obtained.
[0057] Example 6
[0058] 2.1 mol of 2-amino-5-thiocyanatobenzoic acid, 0.5 mol of hydroxyethyldiisopropanolamine and 0.5 mol of triisopropanolamine were added into the reaction kettle in proportion. Under nitrogen protection, the temperature was raised to 98°C with stirring. 13.87 g of chitosan sulfate catalyst and 75.04 g of benzene were added. The temperature was raised to 128°C with stirring. The esterification reaction was carried out for 8.0 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the benzene was removed. Diethanolmonoisopropanolamine was added to adjust the pH value of the system to 7.0, and a sustained-release enhanced cement grinding aid was obtained.
[0059] Example 7
[0060] 2.5 mol of 2-amino-5-thiocyanatobenzoic acid, 0.3 mol of triethanolamine, 0.3 mol of diethanolmonoisopropanolamine and 0.4 mol of triisopropanolamine were added into the reaction kettle in proportion. Under nitrogen protection, the temperature was raised to 99°C with stirring. 16.99 g of chitosan sulfate catalyst and 95.16 g of toluene were added. The temperature was raised to 119°C with stirring. The esterification reaction was carried out for 7.5 hours. During the reaction, the water generated by the reaction was separated. When no more water was separated, the toluene was removed. Triethanolamine was added to adjust the pH value of the system to 6.1, and a sustained-release enhanced cement grinding aid was obtained.
[0061] Example 8
[0062] 2.8 mol of 2-amino-5-thiocyanatobenzoic acid, 0.5 mol of diethanol monoisopropanolamine, 0.1 mol of hydroxyethyl diisopropanolamine and 0.4 mol of triisopropanolamine were added into a reactor in proportion. Under nitrogen protection, the temperature was raised to 100°C with stirring. 21.21 g of chitosan sulfate catalyst and 107.67 g of toluene were added. The temperature was raised to 113°C with stirring. The esterification reaction was carried out for 6.4 hours. During the reaction, the water generated by the reaction was separated. When no more water was separated, the toluene was removed. Triethanolamine and diethanol monoisopropanolamine were added to adjust the pH value of the system to 6.4, and a sustained-release enhanced cement grinding aid was obtained.
[0063] Example 9
[0064] 2.9 mol of 2-amino-5-thiocyanatobenzoic acid, 0.1 mol of triethanolamine, 0.6 mol of hydroxyethyldiisopropanolamine and 0.3 mol of triisopropanolamine were added into a reaction kettle in proportion. Under nitrogen protection, the temperature was raised to 81°C with stirring. 22.53 g of chitosan sulfate catalyst and 112.64 g of benzene were added. The temperature was raised to 124°C with stirring. The esterification reaction was carried out for 2.8 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the benzene was removed. Diethanolmonoisopropanolamine, hydroxyethyldiisopropanolamine and triisopropanolamine were added to adjust the pH value of the system to 7.0, thereby obtaining a sustained-release enhanced cement grinding aid.
[0065] Example 10
[0066] 3.0 mol of 2-amino-5-thiocyanatobenzoic acid, 0.2 mol of triethanolamine, 0.3 mol of diethanol monoisopropanolamine, 0.3 mol of hydroxyethyl diisopropanolamine and 0.2 mol of triisopropanolamine were added into a reaction kettle in proportion. Under nitrogen protection, the temperature was raised to 93°C with stirring. 17.48 g of chitosan sulfate catalyst and 101.96 g of benzene were added. The temperature was raised to 120°C with stirring. The esterification reaction was carried out for 3.1 hours. During the reaction, the water generated by the reaction was separated. After no more water was separated, the benzene was removed. Triethanolamine and diethanol monoisopropanolamine were added to adjust the pH value of the system to 6.0, thereby obtaining a sustained-release enhanced cement grinding aid.
[0067] Comparative Example 1
[0068] Example 5 was repeated, except that the esterification reaction catalyst was replaced with concentrated sulfuric acid, the reaction temperature was replaced with 180° C., and the other process parameters remained unchanged.
[0069] Comparative Example 2
[0070] Example 5 was repeated. After the esterification reaction was completed, the chitosan sulfate catalyst and the reaction mixture were separated using a glass sand core funnel, and the other process parameters remained unchanged.
[0071] Comparative Example 3
[0072] Diethylene glycol among the polyol compounds was selected as a grinding aid for comparison.
[0073] Comparative Example 4
[0074] Diethanol monoisopropanolamine among the polyol amine compounds was selected as a grinding aid for comparison.
[0075] The performance tests and evaluations were conducted on the sustained-release enhanced cement grinding aids prepared in the above specific examples, the substances described in Comparative Examples 1 to 4, and a commercially available cement grinding aid.
[0076] Referring to the test method in GB / T 26748-2011 "Cement Grinding Aids", 5 kg of various cement raw materials were added to the test mill according to the cement ratio of P.O42.5, and the cement ratio was: 83% clinker, 7% fly ash, 5% limestone, and 5% gypsum. Before grinding, the cement grinding aid was added to the cement raw materials, and the grinding time was fixed at 22 minutes. The grinding aid effect and cement performance were evaluated and tested. The slow-release enhanced cement grinding aids prepared in Examples 1 to 10 above, the substances described in Comparative Examples 1 to 4, a commercially available cement grinding aid, and a blank without cement grinding aid were compared and evaluated, and the dosage was 0.03%.
[0077] Table 1
[0078]
[0079]
[0080] As can be seen from Table 1, compared with the blank group, the sustained-release enhanced cement grinding aid prepared by the present invention has a larger specific surface area of PO 42.5 cement after grinding, and smaller 80μm sieve residue and 45μm sieve residue, which has a significant grinding aid effect and is significantly better than the commercially available cement grinding aid. Compared with Comparative Examples 1 to 4, the specific surface area of PO 42.5 cement after grinding is larger, the 80μm sieve residue and 45μm sieve residue are smaller, and the grinding aid effect is better. The results compared with Comparative Example 1 show that the chitosan sulfate catalyst has a higher catalytic efficiency than the conventional concentrated sulfuric acid catalyst, and more target products are obtained to improve its grinding aid effect. The results compared with Comparative Example 2 show that the grinding aid effect of the chitosan sulfate catalyst becomes worse after separation, and the chitosan sulfate catalyst plays a good grinding aid role. The results compared with Comparative Examples 3 and 4 show that the sustained-release enhanced cement grinding aid prepared by the present invention has a better grinding aid effect than conventional small molecule grinding aids due to its molecular size effect.
[0081] Table 2
[0082]
[0083] As can be seen from Table 2, the slow-release enhanced cement grinding aid prepared by the present invention significantly improves the 1d, 3d, 7d, and 28d flexural and compressive strengths of P.O42.5 cement compared with the blank group, and the enhancement effect continues to increase with the increase of age, indicating that it has a significant slow-release enhancement effect and is significantly better than commercially available cement grinding aids. Compared with Comparative Examples 1 to 4, the 1d, 3d, 7d, and 28d flexural and compressive strengths of P.O42.5 cement are significantly improved, and the enhancement effect is better. The results compared with Comparative Example 1 show that the chitosan sulfate catalyst has a higher catalytic efficiency than the conventional concentrated sulfuric acid catalyst, and more target products are obtained to improve its enhancement effect. The results compared with Comparative Example 2 show that the enhancement effect of the chitosan sulfate catalyst becomes worse after separation, and the chitosan sulfate catalyst plays a good enhancement role. The results compared with Comparative Examples 3 and 4 show that the slow-release enhanced cement grinding aid prepared by the present invention continuously releases new alcoholamine compounds due to the continuous hydrolysis of its ester group, continuously promotes cement hydration, and thus achieves a slow-release enhancement effect.
Claims
1. A method for preparing a sustained-release enhanced cement grinding aid, characterized in that The following steps are involved: (1) 2-amino-5-thiocyanatobenzoic acid and polyol amine A are mixed in a reaction kettle, stirred and heated to 80-100° C. under nitrogen protection; the molar ratio of the 2-amino-5-thiocyanatobenzoic acid to the polyol amine is (1-3):1; (2) adding chitosan sulfate catalyst and water-carrying agent, stirring and heating to 110-130°C, and carrying out esterification reaction for 2-8 hours. During the reaction, the water generated by the reaction is separated, and the water-carrying agent is removed after no more water is separated. The amount of chitosan sulfate catalyst used is 2-4% of the mass of 2-amino-5-thiocyanatobenzoic acid; the amount of water-carrying agent used is 15-20% of the mass of 2-amino-5-thiocyanatobenzoic acid; (3) Add polyol amine B to adjust the pH value of the system to 6-7 to obtain a sustained-release enhanced cement grinding aid.
2. The method for preparing the sustained-release enhanced cement grinding aid according to claim 1, characterized in that The polyol amine A is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, and triisopropanolamine, or any mixture thereof; the polyol amine B is one of triethanolamine, diethanol monoisopropanolamine, hydroxyethyl diisopropanolamine, and triisopropanolamine, or any mixture thereof.
3. The method for preparing the sustained-release enhanced cement grinding aid according to claim 1, characterized in that The water-carrying agent is one of benzene and toluene.
4. The method for preparing the sustained-release enhanced cement grinding aid according to claim 1, characterized in that The preparation method of the chitosan sulfate catalyst comprises the following steps: Chitosan is dissolved in an acetic acid solution, diluted sulfuric acid is added to precipitate it and the precipitate is filtered, the precipitate is washed with water until it is neutral, then rinsed with an organic solvent, and dried to obtain a chitosan sulfate catalyst.
5. The method for preparing the sustained-release enhanced cement grinding aid according to claim 4, characterized in that The weight average molecular weight of chitosan is 2×10 5 ~5×10 5 g / mol.
6. The method for preparing the sustained-release enhanced cement grinding aid according to claim 1, characterized in that The 2-amino-5-thiocyanatobenzoic acid is added to the reaction kettle in three times, one third of the total amount is added before the start of the esterification reaction, and then one third of the total amount is added every one third of the esterification reaction until all the 2-amino-5-thiocyanatobenzoic acid is added.
7. The method for preparing the sustained-release enhanced cement grinding aid according to claim 1, characterized in that The dosage of the slow-release enhanced cement grinding aid is 0.02-0.10wt% of the cement.
Citation Information
Patent Citations
Polyolamine ester and its synthesis method and use
CN104311435A
Chitosan sulphate preparation method
CN104448042A